Review of the Thermo-Physical Properties and Performance Characteristics of a Refrigeration System Using Refrigerant-Based Nanofluids - Mahesh Suresh Patil; Sung Chul Kim; Jae-Hyeong Seo; Moo-Yeon Lee (Energies, 2015)
Nanofluids are considered a promising choice for several heat transfer applications. With the increasing awareness for energy saving and efficiency improvement in various thermal systems, including refrigeration systems, there is a growing interest in the refrigerant-based nanofluids owing to their superior thermo-physical properties. Nanorefrigerants are a class of nanofluid, which consist of suspended nanoparticles in a base refrigerant. In this paper, it is intended to include many articles on refrigeration systems that use nanorefrigerants, published in the period from 2005 to 2015. Although this is an extensive review, it could not include all the papers, and only some major research works were selected. It is believed that the dependency of thermal conductivity and other properties on temperature will make the thermal systems more efficient while operating at a high temperature. The literature reviews associated with the performance characteristics of nanorefrigerants in refrigeration systems for the last 10 years have been compiled and presented in this paper. Furthermore, recent studies related to thermo-physical properties of nanorefrigerants and nanolubricants have also been summarized and reviewed in this paper.